1997
DOI: 10.1021/jm9608366
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationships of N2-Aryl-3-(isoxazolylsulfamoyl)-2-thiophenecarboxamides as Selective Endothelin Receptor-A Antagonists

Abstract: We report here that N2-aryl-3-(isoxazolylsulfamoyl)-2-thiophenecarboxamides are potent and selective small molecule ETA receptor antagonists. The aryl group was subjected to extensive structural modification. With monosubstitution, the para position was most useful in increasing potency, with methyl being preferred. With disubstitution, 2,4-disubstitution further enhanced activity with methyl or cyano groups being preferred at the 2-position. In this series, a benzo-[d][1,3]dioxole group is equivalent to a 4-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…[30][31][32] In the initial experiment, effects of sitaxsentan (5 mg/ Since results from several laboratories suggest that kg body weight infused iv) were assessed on mean endothelin mediates effects of both hypoxia and MCT pulmonary arterial pressure (MPAP), mean systemic on the pulmonary vasculature, we have evaluated the arterial pressure (MSAP), and heart rate (HR) of rats ability of sitaxsentan (TBC11251), an orally available, subsequently exposed to acute hypoxia 90 min in highly selective endothelin A receptor antagonist, 33,34 duration. Under pentobarbital sodium anesthesia to prevent hypoxia-and MCT-induced pulmonary and (50 mg/kg ip), a femoral artery and vein were cancardiac changes.…”
Section: -29mentioning
confidence: 99%
“…[30][31][32] In the initial experiment, effects of sitaxsentan (5 mg/ Since results from several laboratories suggest that kg body weight infused iv) were assessed on mean endothelin mediates effects of both hypoxia and MCT pulmonary arterial pressure (MPAP), mean systemic on the pulmonary vasculature, we have evaluated the arterial pressure (MSAP), and heart rate (HR) of rats ability of sitaxsentan (TBC11251), an orally available, subsequently exposed to acute hypoxia 90 min in highly selective endothelin A receptor antagonist, 33,34 duration. Under pentobarbital sodium anesthesia to prevent hypoxia-and MCT-induced pulmonary and (50 mg/kg ip), a femoral artery and vein were cancardiac changes.…”
Section: -29mentioning
confidence: 99%
“…(8)), a compound with good potency, long duration of action and good bioavailability. Wu et al [80] further presented the SAR of one particular thienylsulfonamide series: N 2 -aryl-3-(isoxazolylsulfamoyl)-2-thiophenecarboxamides, a novel series of ET A receptor antagonists consisting of three unitsan isoxazole, a thiophene and an aryl moiety. A sulfonamide group tethers the isoxazole and the thiophene moieties while an amide linkage connects the aryl group and the thiophene.…”
Section: Chan Et Al ( I M M U N O P H a R M A C E U T I C S / T E X mentioning
confidence: 99%
“…They had already shown that isoxazoles with dimethyl substituents are preferred for binding affinity [70,81] and a halogen substitution on the 4-position increases the binding affinity by 3 to 5-fold [18,82]. They, therefore, synthesized [78,80] isoxazolylsulfonamides with chloro, bromo and methyl group at the 4-position of the isoxazole ring as in scheme 9. The aryl group was subjected to extensive structural modification.…”
Section: Chan Et Al ( I M M U N O P H a R M A C E U T I C S / T E X mentioning
confidence: 99%
“…Moreover, the discovery of thiophenesulfonamides, like as sitaxsentan (TBC11251) (Fig. 1), led to potent and selective ET A receptor antagonists [6][7][8][9][10][11][12]. In this paper, continuing our researches [13][14][15] and with the aim to obtain new ET receptor ligands, we report the synthesis and binding test results of a new series of benzenesulfonamides.…”
Section: Introductionmentioning
confidence: 99%
“…dimethyl-5-isoxazolamine (3), commercially available, or with 4-chloro-3-methyl-5-isoxazolamine (4) [6] in the presence of anhydrous pyridine and 4-(dimethylamino) pyridine (DMAP) for compound 5, or in anhydrous tetrahydrofuran and sodium hydride for compounds 6 and 7. This latter method enabled to obtain compound 6 with better yield with respect to the known procedure [16].…”
Section: Introductionmentioning
confidence: 99%